PROTOTYPE OF FAULT DETECTION AND LEAKAGE CURRENT MONITORING ON FL2XCY CABLE BASED ON INTERNET OF THINGS - Perdana Putera Siswanto, Farid; Kustori, Kustori; Dwiyanto, Dwiyanto (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airfield lighting system (ALS) is a visual landing aid that serves to assist and serve aircraft that take off, land and taxi in order to move efficiently and safely. This facility consists of special lights, which provide visual cues and information to pilots, especially when pilots are about to land or take off. The occurrence of interference with the airport lighting system caused by damage to the FL2XCY cable causes the pilot's vision to be less efficient when landing, takeoff and movement on the air side which can later endanger the flight. Therefore, a tool is needed that can detect the location of the disturbance and monitor the current on the cable by using the internet of things (IoT) as a device that transmits output data from sensor readings to the website. In this research, a prototype design will be made that can detect the location of the disturbance and monitor the current on the cable so that it makes it easier to find where the problem and disturbance are located on the cable because the FL2XCY cable is in the ground.